Language Teacher Education and the Developing World: Exploring 'Horizons of Possibility' for Identity and Agency. (23rd May 2016) - Morgan, Brian
Abstract : This article advances a "bottom-up" approach to language policy and planning. Drawing on several recommendations in the Lahore Declaration on Language Sciences and the Developing World (Tupas & Mahboob, 2013), the author examines the ways in which the decision-making capacities of field professions in English Language Teaching (ELT) might be enhanced to further the development goals stated in the declaration. Which theories of language, for example, are more likely to foster teacher agency, or conversely, discourage innovation and local relevance? To realize the former, it is crucial for scholars and practitioners in the developing world to challenge "epistemic dependencies" based on Western-based knowledge in ELT (Kumaravadivelu, 2012). The textual and pedagogical complexities of such a challenge are then explored, followed by a discussion of their possible implementation in a certificate program in the Teaching of English as an International Language (D-TEIL).